Given the function:
![f(x)=3x^2+3x-1_{}](https://img.qammunity.org/2023/formulas/mathematics/college/yf0zlce7nagi9l1s0egsnnk8u7v1x9lxh2.png)
Let's find the following:
• (a). f(0)
To solve for f(0), substitue 0 for x and evaluate.
![\begin{gathered} f(0)=3(0)^2+3(0)-1^{} \\ \\ f(0)=3(0*0)+3(0)-1 \\ \\ f(0)=3(0)+3(0)-1 \\ \\ f(0)=0+0-1 \\ \\ f(0)=-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w8tyr187vzgl3yxpkwdvrfxjdbmt8bdt5w.png)
• b). f(2)
To solve for f(2), substitute 2 for x and evaluate:
![\begin{gathered} f(2)=3(2)^2+3(2)-1 \\ \\ f(2)=3(2*2)+3(2)-1 \\ \\ f(2)=3(4)+3(2)-1 \\ \\ f(2)=12+6-1 \\ \\ f(2)=18-1 \\ \\ f(2)=17 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/fnenhtzm7dgspg1hhmrdccedqh5lklu73k.png)
• (c). f(-2)
To solve for for f(-2), substitute -2 for x and evaluate:
![\begin{gathered} f(-2)=3(-2)^2+3(-2)-1 \\ \\ f(-2)=3(4)-6-1 \\ \\ f(-2)=12-6-1 \\ \\ f(-2)=5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hikqdnanm96rcnj7rck8y7yxleraqorkoa.png)
• d). f(b)
To solve for f(b) substitute b for x and evalaute:
![\begin{gathered} f(b)=3(b)^2+3(b)-1 \\ \\ f(b)=3(b* b)+3(b)-1 \\ \\ f(b)=3b^2+3b-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r5r0pj4znws2podydd4oz8t1i25k9k5yus.png)
• e). f(2a)
Substitute 2a for x:
![\begin{gathered} f(2a)=3(2a)^2+3(2a)-1 \\ \\ f(2a)=3(2a*2a)+3(2a)-1 \\ \\ f(2a)=3(4a^2)+3(2a)-1 \\ \\ f(2a)=12a^2+6a-1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5ngk0iebcvq6o1up6unryi825jradqr8o5.png)
ANSWER:
a. f(0) = -1
b. f(2) = 17
c. f(-2) = 5
d. f(b) = 3b² + 3b - 1
e. f(2a) = 12a² + 6a - 1